Composite Backstepping Consensus Algorithms of Leader-Follower Higher-Order Nonlinear Multiagent Systems Subject to Mismatched Disturbances - Wang, Xiangyu; Li, Shihua; Chen, Michael Z. Q. (IEEE transactions on cybernetics, 2018)
This paper is devoted to solving the output consensus problem of leader-follower higher-order nonlinear multiagent systems subject to mismatched disturbances. The disturbances are allowed to be in higher-order forms. First, by constructing a generalized proportional-integral observer for each follower, estimates of the disturbances and their derivatives are obtained. At the same time, a distributed observer is also developed for the followers to estimate the leader state information. Second, based on the estimates of the disturbances and the leader state, together with the backstepping technique, a feedforward-feedback composite consensus control scheme is proposed. The designed distributed protocols guarantee asymptotic output consensus for the agents. Simulation results validate the effectiveness of the proposed composite control scheme.